2009
DOI: 10.1080/13697130902912605
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters linked with malignancy in endometrial polyps

Abstract: The prevalence of premalignant and malignant endometrial polyps is very low. Advanced age, menopause, obesity and diabetes increase the risk of endometrial polyp malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 22 publications
1
41
3
14
Order By: Relevance
“…Obese women have higher levels of circulating estrogen which stimulate the endometrium to create endometrial polyps and probably malignant endometrial polyps [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese women have higher levels of circulating estrogen which stimulate the endometrium to create endometrial polyps and probably malignant endometrial polyps [27].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested that larger polyps are associated with a higher risk of malignancy [21,25]. However, others stated that polyp size is not a distinctive feature of malignancy [27,31]. A recently published meta-analysis concluded that the authors reported the size of polyps in centimeters, millimeters, grams, and milliliters, making the analysis of this association more difficult [32].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is considered to be a risk factor for the development of EPs themselves (21), and in particular appears to lead to malignant progression (22)(23)(24). In a study by Litta et al (25) a linear correlation between BMI and risk of malignancy in women with EPs was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In four studies, larger polyps were directly associated with a greater risk of malignancy. According to Fernández-Parra et al 26 , Goldstein et al 3 , Shushan, Revel and Rojansky 27 , and Gregoriou et al 28 , polyp size did not represent a risk factor for malignancy. The authors highlight that in this meta-analysis, polyp size was reported in different units of measurement (centimeters, millimeters, or grams) and data were not amenable; these factors hindered the analysis of this association.…”
Section: Sensivitymentioning
confidence: 95%